Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad E6 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging

Bouvetøya proclaimed a nature reserve (Polar Record, 1972)
Publisher: Cambridge University Press
Keywords: Bouvetøya; lovgivning

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet C7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet B7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970 - Adie, Raymond J. (Universitetsforlaget, 1972)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Sperm whales of the southeast pacific. Part III : Norphometry - Clarke, Robert; Paliza, Obla (Universitetsforlaget, 1972)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

Fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1972)
Keywords: Antarktis; paleontologi

Diurnal variations of the surface wind over the Antarctic ice shelf - Hisdal, Vidar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

Diurnal wind variations in Antarctica - Hisdal, Vidar (Quarterly Journal of the Royal Meteorological Society, 1972)
For the three Antarctic ice shelf stations considered (Norway Station, Maudheim, and Halley Bay) it is shown that from spring to autumn a systematic diurnal variation of the mean vector wind at the surface exists. Different factors that may be responsible for this variation are discussed. The results seem to agree well with the assumption that in areas far from the ice front (the seaward edge of the ice shelf) the main cause is the larger net gain of momentum in the lowest layers during the middle of the day, while closer to the ice front there is an additional effect of the varying contrast between the air temperature over the sea and over the ice shelf.
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Konferansepublikasjon Series B (International Union of Geological Sciences) (0332-5172)
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi

Lichens from Vestfjella, Dronning Maud Land - Lindsay, Denis Christopher (Norsk Polarinstitutt, 1972)
Publication Title: Meddelelser
Keywords: Dronning Maud Land; botanikk; lav; planter

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Publication Title: Institute of polar studies. Report
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi

Joh. N. Tønnessen: Den moderne hvalfangst historie. Opprinelse og utvikling. Bind 2-4. Utgitt av Norges hvalfangstforbund, Sandefjord 1967, 1969, 1970. - Solhaug, Trygve (Historisk tidsskrift, 1972)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

The Norwegian Antarctic Expedition 1970-1971 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1970-71; biologi; geologi; glasiologi